Standardization, validation, and comparative evaluation of a convenient surrogate recombinant vesicular stomatitis virus plaque reduction test for quantification of Hantaan orthohantavirus (HTNV) neutralizing antibodies - Jing Wei; Hui Zhang; Jiawei Pei; Qiqi Yang; Yuan Wang; Xiaolei Jin; He Liu; Liang Zhang; Hongwei Ma; Linfeng Cheng; Yangchao Dong; Yingfeng Lei; et al. (Virology Journal)
Abstract Hantaan orthohantavirus (HTNV) is responsible for severe hemorrhagic fever with renal syndrome (HFRS), which has a case fatality rate of 1% to 10%. Currently, the inactive vaccine licensed in endemic areas elicit low levels of neutralizing antibodies (NAbs). Early NAbs administration is helpful for patients recovery from HFRS. Therefore, measuring NAbs is crucial for evaluating the immune response following infection or vaccination. The golden standard for HTNV NAbs measurement is the focus reduction neutralization test (FRNT), which typically requires skilled technicians and is performed under high biosafety containment facility. Here, we established a surrogate NAbs titration method with replication-competent vesicular stomatitis virus (VSV) bearing HTNV glycoprotein (rVSV-HTNV-GP) based plaque reduction neutralization test (PRNT). Then compared and correlated this method with the authentic HTNV based FRNT, and applied it to measure the NAbs level in 47 serum samples from HFRS patients, healthy donors and inactive vaccine recipients. We observed positive correlations between two neutralization assays among HFRS patients and inactive vaccine recipients (R2 = 0.5994 and 0.3440, respectively) and confirmed the clear specificity with healthy donors without vaccinated and reproducibility with three more assays. Our results suggest that rVSV-HTNV-GP based PRNT is a reliable lower-biosafety level surrogate for HTNV NAbs evaluation, which is easy to perform with higher sensitivity. Graphical abstract